2018
DOI: 10.21061/jcte.v32i1.1590
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors in a High School Healthcare Education Program

Abstract: Research has demonstrated career and technical education (CTE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…One intervention pathway may be to encourage students to become involved in targeted programs, activities or technological career paths promoted within their school. Partaking in career-focused or hands-on school-to-work programs may lead students to develop new interests, better relationships with specific teachers, and increased hopes for future employment (Thessin, Scully-Russ, & Lieberman, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…One intervention pathway may be to encourage students to become involved in targeted programs, activities or technological career paths promoted within their school. Partaking in career-focused or hands-on school-to-work programs may lead students to develop new interests, better relationships with specific teachers, and increased hopes for future employment (Thessin, Scully-Russ, & Lieberman, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These differential outcomes suggest unequal treatment, but few research articles addressed the underlying mechanisms (Rose, 2012). The literature also suggested that schools that focus on supporting all CTE students in completing their pathway or program requirements, through flexible scheduling, transportation, and wraparound services (e.g., child care, counseling; Thessin et al, 2017), show promise for equity.…”
Section: What Observed Differences In Academic and Social And Emotionalmentioning
confidence: 99%
“…In this case, institutions of secondary vocational education and the employer jointly design and implement education programme. The latter is in order to learn the conditions that increase teaching and learning effectiveness and to build their models to improve education quality (Thessin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%